Low-odor and high-efficiency antibacterial polypropylene composite material for gas-assisted molding and preparation method of low-odor and high-efficiency antibacterial polypropylene composite material
By developing low-odor, high-efficiency antibacterial polypropylene composite materials for gas-assisted molding, the defects such as uneven wall thickness and surface scars in the gas-assisted molding process are solved, and low-odor, high-efficiency antibacterial properties are achieved to meet the needs of the automotive interior market.
Patent Information
- Application Number
- CN202411962599.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
The existing polypropylene materials are prone to cause defects such as uneven wall thickness, surface scars, and bubbles in the gas-assisted molding process, and it is difficult to meet the demand for low-odor and efficient antibacterial materials in automotive interiors.
A low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding is developed. By reasonably proportioning polypropylene, toughener, filler, tetrafluoroethylene, antibacterial agent, deodorant, coupling agent, auxiliary agent and masterbatch, combined with high-speed stirring and twin-screw extrusion process, the odor is further processed through a homogenized baking system to reduce the odor.
It has achieved good mechanical properties of the products, and has low odor and high-efficiency antibacterial properties. The antibacterial rate reaches more than 99.9%, and the odor level reaches Volkswagen level 3.0, meeting the needs of the automotive interior market.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and a preparation method thereof. Background Art
[0002] Polypropylene is widely used in the manufacture of automotive interior parts, such as dashboards, door panels, and auxiliary dashboards, due to its advantages such as non-toxicity, acid and alkali resistance, low water absorption, easy processing, and good dimensional stability. As people's requirements for quality of life increase, health issues are becoming more and more important. With the development of the automotive industry, the health of the interior environment of the car has received more and more attention from consumers, especially with the development of shared travel. More and more people will indirectly contact other people through the car interior. Car interior products often come into contact with human skin, and a large number of bacteria are often attached to the surface of the products. These harmful bacteria will continue to spread and transfer, threatening the health of people who have come into contact with them.
[0003] The parts of the car interior that come into contact with the human body most frequently are door handles, roof handles, sun visor frames, etc., and most of these parts are injection molded using a gas-assisted molding process. The principle of this process is to use high-pressure inert gas (mainly N2) to produce a hollow section inside the plastic part, and use gas pressure maintenance instead of plastic injection pressure maintenance to eliminate product shrinkage marks and complete the injection molding process. Since the gas is injected into the polymer melt, gas-assisted molding technology has the advantages of improving the surface quality of the product, saving raw materials, shortening the production cycle, and reducing problems such as part warping. It is an important process for achieving lightweight automobiles, but this process is prone to defects such as uneven product wall thickness, surface scars, and bubbles during the injection molding process. Therefore, the preparation of low-odor, high-efficiency antibacterial polypropylene composite materials for gas-assisted molding has become a top priority to meet the actual needs of the automotive industry for material development. Summary of the invention
[0004] The present invention aims to meet the demand for polypropylene materials in the automotive interior market, thereby developing a low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding, which is applied to automotive interior parts that require gas-assisted molding technology injection molding, so that the products have good mechanical properties and low-odor, high-efficiency antibacterial properties.
[0005] One of the purposes of the present invention is to provide a low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding. The material is composed of the following raw materials: polypropylene, toughening agent, filler, tetrafluoroethylene, antibacterial agent, deodorant, coupling agent, other additives, masterbatch, etc. The specific weight percentages are as follows:
[0006]
[0007] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and its preparation method are characterized in that under the test conditions of 230°C*2.16Kg, the polypropylene is one or a mixture of copolymer polypropylenes with a melt flow rate of 50 to 100 g / 10min;
[0008] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and its preparation method are characterized in that the toughening agent is at least one of a thermoplastic polyurethane elastomer with a hardness of 20D to 45D or an ethylene-octene copolymer;
[0009] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and its preparation method are characterized in that the filler is one or a mixture of talcum powder, magnesium sulfate whisker, calcium carbonate, glass microbeads;
[0010] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and its preparation method are characterized in that the polytetrafluoroethylene is an ultrafine powder with a porous structure and a particle size of 1-20 μm, which can improve the melt strength and crystallinity of the matrix polypropylene on the one hand, and at the same time, its own ultrafine porous structure also enables it to obtain a uniform wall thickness and a better appearance in gas-assisted molding injection molding;
[0011] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and its preparation method are characterized in that the antibacterial agent is one or more of rod-shaped nano zinc oxide, silver-zinc compound antibacterial agent, and polyquaternary ammonium salt, which is non-toxic, harmless, green and environmentally friendly, and complies with the relevant requirements of the EU ROHS directive;
[0012] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and its preparation method are characterized in that the deodorant is a mixture of one or more porous inorganic silicate, nano-scale attapulgite, or micron-scale zeolite powder;
[0013] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and its preparation method are characterized in that the coupling agent is a silane coupling agent or a phosphate coupling agent;
[0014] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and its preparation method are characterized in that the other additives include one or a mixture of light stabilizers, lubricants, and antioxidant masterbatches;
[0015] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and the preparation method thereof are characterized in that the light stabilizer is a hindered amine light stabilizer;
[0016] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and its preparation method are characterized in that the lubricant is one or a mixture of zinc stearate, calcium stearate, and magnesium stearate;
[0017] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and its preparation method are characterized in that the antioxidant masterbatch is a composite synergistic antioxidant of a main antioxidant (phenols), an auxiliary antioxidant (phosphites) and an epoxy resin, wherein the melting temperature of the main antioxidant DSC is 110-125°C, the melting temperature of the auxiliary antioxidant DSC is 180-190°C, and the melting temperature of the epoxy resin DSC is 120-160°C;
[0018] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and its preparation method are characterized in that the masterbatch is an inorganic black masterbatch;
[0019] The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and its preparation method are as follows:
[0020] Step 1: Prepare by weighing polypropylene, toughening agent, filler, tetrafluoroethylene, antibacterial agent, deodorant, coupling agent, other additives and masterbatch according to weight ratio;
[0021] Step 2: Put the polypropylene, toughening agent, filler and tetrafluoroethylene in step 1 into a high-speed mixer and mix them at room temperature for about 10 minutes. Add antibacterial agent, deodorant, coupling agent, other additives, masterbatch and other components and mix them for 20 minutes until they are uniform.
[0022] Step 3: The extrusion temperatures in the screw are: 180-200°C in zone 1, 200-225°C in zone 2, 200-225°C in zone 3, 200-215°C in zone 4, 190-210°C in zone 5, and the screw speed is 350-400r / min.
[0023] Step 4: After the twin screw is heated to the test temperature, the mixture obtained in step 2 is melt blended and extruded in a twin screw extruder, then cooled in water, dried, pelletized, and finally enters the homogenization and drying system. The drying system adopts three-tank dynamic cycle drying, and a cooling tank is added. The high-temperature material is blown and cooled in an additional silo to allow the odor small molecules to fully volatilize, thereby helping to improve the odor. The drying process is 130℃*6h to finally obtain the finished product.
[0024] The application of a low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding; characterized in that the polypropylene composite material is suitable for gas-assisted molding technology, and at the same time the antibacterial rate reaches more than 99.9%, the odor level reaches Volkswagen level 3.0, and the antibacterial performance of the material after long-term testing can also reach more than 99%, meeting the application needs of the automotive interior market. DETAILED DESCRIPTION
[0025] Example 1
[0026] A low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and a preparation method thereof, wherein the raw materials for the preparation thereof comprise the following components, by weight: 57 parts of copolymerized polypropylene (SK, South Korea, brand: BX3900, melt index 60 g / 10 min), 15 parts of TPEE (DuPont, brand: 5526, melt index 18 g / 10 min), 7 parts of talcum powder (commercially available, mesh number: 10000 mesh), 10 parts of magnesium sulfate whisker (commercially available, mesh number: 10000 mesh), 10 parts of tantalum powder ... The ingredients include: 1) fluorocarbon (commercially available, diameter <1 μm) 3 parts, PTFE (commercially available, mesh number: 10000 mesh) 10 parts, antibacterial agent (commercially available, brand: Z20Y) 0.3 parts, deodorant (commercially available, porous inorganic silicate) 2 parts, coupling agent (commercially available, silane coupling agent) 2 parts, light stabilizer (commercially available, 802PP5) 0.5 parts, lubricant (commercially available, zinc stearate) 0.52 parts, antioxidant masterbatch (homemade) 1.5 parts, and color masterbatch 1 part.
[0027] The weighed polypropylene, toughening agent, filler and tetrafluoroethylene were put into a high-speed mixer and mixed at room temperature for about 10 minutes. Antibacterial agent, deodorant, coupling agent, other additives, masterbatch and other components were added and mixed for 20 minutes until uniform. The mixture was added into a twin-screw extruder. The temperatures of each section of the extruder were: 180°C in zone 1, 200°C in zone 2, 210°C in zone 3, 210°C in zone 4 and 200°C in zone 5. After the twin screw was heated to the test temperature, the screw speed was set to 350r / min, and the mixed mixture was melt-blended in the twin-screw extruder. After extrusion, it was cooled by water, dried and pelletized, and finally entered the homogenization and drying system. The drying process was 130°C*6h to finally obtain the product.
[0028] The product particles were placed at room temperature for 24 hours and then tested for odor and melt flow rate. The polypropylene particles were made into 170*10*4mm strips, 80*10*4mm strips, and 150*100*3.2mm plain boards using an injection molding machine. The strips and boards were then placed at room temperature for 24 hours and then tested for mechanical properties and antibacterial properties. At the same time, the plain boards were subjected to thermal oxygen aging and light aging experiments, and finally an antibacterial test was performed.
[0029] Example 2
[0030] A low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and a preparation method thereof, wherein the raw materials for the preparation thereof comprise the following components, by weight: 55 parts of copolymerized polypropylene (SK, South Korea, brand: BX3900, melt index 60 g / 10 min), 15 parts of TPEE (DuPont, brand: 5526, melt index 18 g / 10 min), 7 parts of talcum powder (commercially available, mesh number: 10000 mesh), 7 parts of magnesium sulfate whisker (commercially available, mesh number: 10000 mesh), 10 parts of tantalum powder ... The ingredients include: 1) fluorocarbon (commercially available, diameter <1 μm) 3 parts, PTFE (commercially available, mesh number: 10000 mesh) 12 parts, antibacterial agent (commercially available, brand: Z20Y) 0.3 parts, deodorant (commercially available, porous inorganic silicate) 2 parts, coupling agent (commercially available, silane coupling agent) 2 parts, light stabilizer (commercially available, 802PP5) 0.5 parts, lubricant (commercially available, zinc stearate) 0.52 parts, antioxidant masterbatch (homemade) 1.5 parts, and color masterbatch 1 part.
[0031] The weighed polypropylene, toughening agent, filler and tetrafluoroethylene were put into a high-speed mixer and mixed at room temperature for about 10 minutes. Antibacterial agent, deodorant, coupling agent, other additives, masterbatch and other components were added and mixed for 20 minutes until uniform. The mixture was added into a twin-screw extruder. The temperatures of each section of the extruder were: 180°C in zone 1, 200°C in zone 2, 210°C in zone 3, 210°C in zone 4 and 200°C in zone 5. After the twin screw was heated to the test temperature, the screw speed was set to 350r / min, and the mixed mixture was melt-blended in the twin-screw extruder. After extrusion, it was cooled by water, dried and pelletized, and finally entered the homogenization and drying system. The drying process was 130°C*6h to finally obtain the product.
[0032] The product particles were placed at room temperature for 24 hours and then tested for odor and melt flow rate. The polypropylene particles were made into 170*10*4mm strips, 80*10*4mm strips, and 150*100*3.2mm plain boards using an injection molding machine. The strips and boards were then placed at room temperature for 24 hours and then tested for mechanical properties and antibacterial properties. At the same time, the plain boards were subjected to thermal oxygen aging and light aging experiments, and finally an antibacterial test was performed.
[0033] Example 3
[0034] A low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and a preparation method thereof, wherein the raw materials for the preparation thereof comprise the following components, by weight: 52 parts of copolymerized polypropylene (SK, South Korea, brand: BX3900, melt index 60 g / 10 min), 15 parts of TPEE (DuPont, brand: 5526, melt index 18 g / 10 min), 7 parts of talcum powder (commercially available, mesh number: 10000 mesh), 7 parts of magnesium sulfate whisker (commercially available, mesh number: 10000 mesh), 10 parts of tantalum powder ... The ingredients include: 1) fluorocarbon (commercially available, diameter <1 μm) 3 parts, PTFE (commercially available, mesh number: 10000 mesh) 15 parts, antibacterial agent (commercially available, brand: Z20Y) 0.3 parts, deodorant (commercially available, porous inorganic silicate) 2 parts, coupling agent (commercially available, silane coupling agent) 2 parts, light stabilizer (commercially available, 802PP5) 0.5 parts, lubricant (commercially available, zinc stearate) 0.52 parts, antioxidant masterbatch (homemade) 1.5 parts, and color masterbatch 1 part.
[0035] The weighed polypropylene, toughening agent, filler and tetrafluoroethylene were put into a high-speed mixer and mixed at room temperature for about 10 minutes. Antibacterial agent, deodorant, coupling agent, other additives, masterbatch and other components were added and mixed for 20 minutes until uniform. The mixture was added into a twin-screw extruder. The temperatures of each section of the extruder were: 180°C in zone 1, 200°C in zone 2, 210°C in zone 3, 210°C in zone 4 and 200°C in zone 5. After the twin screw was heated to the test temperature, the screw speed was set to 350r / min, and the mixed mixture was melt-blended in the twin-screw extruder. After extrusion, it was cooled by water, dried and pelletized, and finally entered the homogenization and drying system. The drying process was 130°C*6h to finally obtain the product.
[0036] The product particles were placed at room temperature for 24 hours and then tested for odor and melt flow rate. The polypropylene particles were made into 170*10*4mm strips, 80*10*4mm strips, and 150*100*3.2mm plain boards using an injection molding machine. The strips and boards were then placed at room temperature for 24 hours and then tested for mechanical properties and antibacterial properties. At the same time, the plain boards were subjected to thermal oxygen aging and light aging experiments, and finally an antibacterial test was performed.
[0037] Comparative Example 1
[0038] A low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and a preparation method thereof. The preparation raw materials thereof comprise the following components, measured in parts by weight: 52 parts of copolymerized polypropylene (SK of South Korea, brand: BX3900, melt index 60g / 10min), 15 parts of TPEE (DuPont, brand: 5526, melt index 18g / 10min), 7 parts of talcum powder (commercially available, mesh number: 10000 mesh), 3 parts of magnesium sulfate whiskers (commercially available, diameter <1μm), 15 parts of polytetrafluoroethylene (commercially available, mesh number: 10000 mesh), 2 parts of deodorant (commercially available, porous inorganic silicate), 2 parts of coupling agent (commercially available, silane coupling agent), 0.5 parts of light stabilizer (commercially available, 802PP5), 0.52 parts of lubricant (commercially available, zinc stearate), 1.5 parts of antioxidant masterbatch (self-made), and 1 part of masterbatch.
[0039] The weighed polypropylene, toughening agent, filler and tetrafluoroethylene were put into a high-speed mixer and mixed at room temperature for about 10 minutes. Deodorant, coupling agent, other additives, masterbatch and other components were added and mixed for 20 minutes until uniform. The mixture was added into a twin-screw extruder. The temperatures of each section of the extruder were: 180°C in zone 1, 200°C in zone 2, 210°C in zone 3, 210°C in zone 4 and 200°C in zone 5. After the twin screw was heated to the test temperature, the screw speed was set to 350r / min, and the mixed mixture was melt-blended in the twin-screw extruder. After extrusion, the mixture was cooled by water, dried and pelletized, and finally entered the homogenization and drying system. The drying process was 130°C*6h to finally obtain the product.
[0040] The product particles were placed at room temperature for 24 hours and then tested for odor and melt flow rate. The polypropylene particles were made into 170*10*4mm strips, 80*10*4mm strips, and 150*100*3.2mm plain boards using an injection molding machine. The strips and boards were then placed at room temperature for 24 hours and then tested for mechanical properties and antibacterial properties. At the same time, the plain boards were subjected to thermal oxygen aging and light aging experiments, and finally an antibacterial test was performed.
[0041] Comparative Example 2
[0042] A low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and a preparation method thereof. The preparation raw materials thereof comprise the following components, measured in parts by weight: 59 parts of copolymerized polypropylene (SK of South Korea, brand: BX3900, melt index 60g / 10min), 15 parts of TPEE (DuPont, brand: 5526, melt index 18g / 10min), 7 parts of talcum powder (commercially available, mesh number: 10000 mesh), 3 parts of magnesium sulfate whiskers (commercially available, diameter <1μm), 10 parts of polytetrafluoroethylene (commercially available, mesh number: 10000 mesh), 0.3 parts of antibacterial agent (commercially available, brand: Z20Y), 2 parts of coupling agent (commercially available, silane coupling agent), 0.5 parts of light stabilizer (commercially available, 802PP5), 0.52 parts of lubricant (commercially available, zinc stearate), 1.5 parts of antioxidant masterbatch (self-made), and 1 part of masterbatch.
[0043] The weighed polypropylene, toughening agent, filler and tetrafluoroethylene were put into a high-speed mixer and mixed at room temperature for about 10 minutes. Antibacterial agent, coupling agent, other additives, masterbatch and other components were added and mixed for 20 minutes until uniform. The mixture was added into a twin-screw extruder. The temperatures of each section of the extruder were: 180°C in zone 1, 200°C in zone 2, 210°C in zone 3, 210°C in zone 4 and 200°C in zone 5. After the twin screw was heated to the test temperature, the screw speed was set to 350r / min, and the mixed mixture was melt-blended in the twin-screw extruder. After extrusion, it was cooled by water, dried and pelletized, and finally entered the homogenization and drying system. The drying process was 130°C*6h to finally obtain the product.
[0044] The product particles were placed at room temperature for 24 hours and then tested for odor and melt flow rate. The polypropylene particles were made into 170*10*4mm strips, 80*10*4mm strips, and 150*100*3.2mm plain boards using an injection molding machine. The strips and boards were then placed at room temperature for 24 hours and then tested for mechanical properties and antibacterial properties. At the same time, the plain boards were subjected to thermal oxygen aging and light aging experiments, and finally an antibacterial test was performed.
[0045] Comparative Example 3
[0046] A low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding and a preparation method thereof. The preparation raw materials thereof comprise the following components, measured in parts by weight: 67 parts of copolymerized polypropylene (SK of South Korea, brand: BX3900, melt index 60g / 10min), 15 parts of POE (Mobil, brand: 168, melt index: 2g / 10min), 7 parts of talcum powder (commercially available, mesh number: 10000 mesh), 3 parts of magnesium sulfate whiskers (commercially available, diameter <1μm), 0.6 parts of antibacterial agent (commercially available, brand: Z20Y), 2 parts of deodorant (commercially available, porous inorganic silicate), 2 parts of coupling agent (commercially available, silane coupling agent), 0.5 parts of light stabilizer (commercially available, 802PP5), 0.52 parts of lubricant (commercially available, zinc stearate), 1.5 parts of antioxidant masterbatch (self-made), and 1 part of masterbatch.
[0047] The weighed polypropylene, toughening agent, filler and tetrafluoroethylene were put into a high-speed mixer and mixed at room temperature for about 10 minutes. Antibacterial agent, deodorant, coupling agent, other additives, masterbatch and other components were added and mixed for 20 minutes until uniform. The mixture was added into a twin-screw extruder. The temperatures of each section of the extruder were: 180°C in zone 1, 200°C in zone 2, 210°C in zone 3, 210°C in zone 4 and 200°C in zone 5. After the twin screw was heated to the test temperature, the screw speed was set to 350r / min, and the mixed mixture was melt-blended in the twin-screw extruder. After extrusion, it was cooled by water, dried and pelletized, and finally entered the homogenization and drying system. The drying process was 130°C*6h to finally obtain the product.
[0048] The product particles were placed at room temperature for 24 hours and then tested for odor and melt flow rate. The polypropylene particles were made into 170*10*4mm strips, 80*10*4mm strips, and 150*100*3.2mm plain boards using an injection molding machine. The strips and boards were then placed at room temperature for 24 hours and then tested for mechanical properties and antibacterial properties. At the same time, the plain boards were subjected to thermal oxygen aging and light aging experiments, and finally an antibacterial test was performed.
[0049] Performance evaluation method and implementation standards:
[0050] Tensile strength: tested according to ISO 527-2, tensile rate 50mm / min;
[0051] Flexural modulus: tested in accordance with ISO 178, span 64 mm, test speed 2 mm / min;
[0052] Notched impact strength: tested according to ISO 179-1, 23°C, 4J pendulum;
[0053] Melt flow rate: tested according to ISO 1133-1, 230°C, 2.16kg.
[0054] Odor: Tested according to PV3900, 80℃, 2h.
[0055] Antibacterial performance: The particles were injected into 150*100*3.2mm samples by injection molding machine and tested according to GB / T 31402;
[0056] Mildew resistance: The particles are injected into 150*100*3.2mm samples by injection molding machine and tested according to GB / T 24128;
[0057] Antibacterial performance after thermal oxidative aging: The particles were injected into 150*100*3.2mm samples by injection molding machine, and the samples were placed in a 150℃ oven for 400h and then taken out and tested according to GB / T 31402;
[0058] Antibacterial performance after light aging: The particles were injected into 150*100*3.2mm samples by injection molding machine, and the samples were tested according to SAEJ2412 with irradiation energy of 1240.8KJ, and then tested according to GB / T 31402;
[0059] Gas-assisted molding verification: Prepare the gas-assisted ceiling handle parts through an injection molding machine and observe the surface appearance of the product.
[0060] Table 1 Material formula of Examples 1 to 3 and Comparative Examples 1 to 3 (weight %)
[0061]
[0062] Table 2 Performance of Examples 1 to 3 and Comparative Examples 1 to 3
[0063]
[0064]
[0065] 1. Compared with the prior art, the present invention has the following advantages: suitable for gas-assisted injection molding, low odor, and high efficiency antibacterial.
[0066] 2. The present invention uses TPEE as a toughening agent, which can cooperate with polytetrafluoroethylene in the system to increase the melt strength and crystallization rate of the matrix, thereby reducing excessive infiltration of gas molecules during gas-assisted molding and injection molding to form a product with higher surface quality;
[0067] 3. The present invention uses rod-shaped nano zinc oxide as an antibacterial agent. When the addition amount is no more than 1%, it can have efficient and lasting antibacterial properties. At the same time, its structure can also improve the modulus of the base material and obtain excellent mechanical properties. The deodorant uses porous inorganic silicate, and the post-processing baking process reduces the odor of the material to the mass 3.0 level, meeting the demand of the automotive interior market for low-odor materials.
Claims
1. A low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding, characterized in that: The invention is composed of the following raw materials in percentage by weight: polypropylene: 50-80%; toughening agent: 5-20%; filler: 0-20%; polytetrafluoroethylene: 5-10%; antibacterial agent: 0.5-5%; deodorant: 0.5-3%; coupling agent: 0.5-2%; other additives: 0.5-2%; and masterbatch 0.5-1%.
2. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 1, characterized in that: Under the test condition of 230° C.*2.16 Kg, the polypropylene is one or a mixture of copolymerized polypropylenes having a melt flow rate of 50 to 100 g / 10 min.
3. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 1, characterized in that: The toughening agent is at least one of a thermoplastic polyurethane elastomer with a hardness of 20D to 45D or an ethylene-octene copolymer.
4. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 1, characterized in that: The filler is one or a mixture of talcum powder, magnesium sulfate whisker, calcium carbonate and glass microbeads.
5. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 1, characterized in that: The polytetrafluoroethylene is an ultrafine powder with a porous structure and a particle size of 1-20 μm. On the one hand, it can improve the melt strength and crystallinity of the matrix polypropylene. At the same time, its own ultrafine porous structure also enables it to obtain parts with uniform wall thickness and better appearance in gas-assisted injection molding.
6. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 1, characterized in that: The antibacterial agent is one or more of rod-shaped nano zinc oxide, silver-zinc compound antibacterial agent, and polyquaternium salt, which is non-toxic, harmless, green and environmentally friendly, and complies with the relevant requirements of the EU ROHS directive.
7. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 1, characterized in that: The deodorant is a mixture of one or more porous inorganic silicate, nano-sized attapulgite, or micron-sized zeolite powder.
8. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 1, characterized in that: The coupling agent is a silane coupling agent or a phosphate coupling agent.
9. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 1, characterized in that: The other additives include light stabilizers, lubricants, antioxidant masterbatches or a mixture of several of them.
10. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 9, characterized in that: The light stabilizer is a hindered amine light stabilizer.
11. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 9, characterized in that: The lubricant is one or a mixture of zinc stearate, calcium stearate and magnesium stearate.
12. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 9, characterized in that The antioxidant masterbatch is a composite synergistic antioxidant of a main antioxidant, an auxiliary antioxidant and an epoxy resin, wherein the melting temperature of the main antioxidant DSC is 110-125°C, the melting temperature of the auxiliary antioxidant DSC is 180-190°C, and the melting temperature of the epoxy resin DSC is 120-160°C.
13. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 1, characterized in that: The masterbatch is an inorganic black masterbatch.
14. The low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding according to claim 1, characterized in that: The steps are as follows: Step 1: Prepare by weighing polypropylene, toughening agent, filler, tetrafluoroethylene, antibacterial agent, deodorant, coupling agent, other additives and masterbatch according to weight ratio; Step 2: Put the polypropylene, toughening agent, filler and tetrafluoroethylene in step 1 into a high-speed mixer and mix them at room temperature for about 10 minutes. Add antibacterial agent, deodorant, coupling agent, other additives, masterbatch and other components and mix them for 20 minutes until they are uniform. Step 3: The extrusion temperatures in the screw are: 180-200°C in zone 1, 200-225°C in zone 2, 200-225°C in zone 3, 200-215°C in zone 4, 190-210°C in zone 5, and the screw speed is 350-400r / min; Step 4: After the twin screw is heated to the test temperature, the mixture obtained in step 2 is melt blended and extruded in a twin screw extruder, then cooled in water, dried, pelletized, and finally enters the homogenization and drying system. The drying system adopts three-tank dynamic cycle drying, and a cooling tank is added. The high-temperature material is blown and cooled in an additional silo to allow the odor small molecules to fully volatilize, thereby helping to improve the odor. The drying process is 130℃*8h to finally obtain the finished product.
15. Application of a low-odor, high-efficiency antibacterial polypropylene composite material for gas-assisted molding in automotive interior parts.
16. The use according to claim 15, characterized in that: The polypropylene composite material is suitable for gas-assisted molding technology, and its antibacterial rate reaches more than 99.9%, and its odor level reaches the public level 3.
0. After long-term testing, the antibacterial performance of the material can also reach more than 99%.
Citation Information
Patent Citations
Antibacterial and low-odor decorative polypropylene material used in saloon car and preparation method thereof
CN102020809A
Method for improving stability of polypropylene melt
CN102875889A
Low-oriented extrusion grade polypropylene material and preparation method thereof
CN104130508A
Polypropylene composition and preparation method thereof
CN107629314A
Low-density polypropylene foam with heat insulation performance and preparation method and application thereof
CN111171452A